2013
DOI: 10.1111/aji.12107
|View full text |Cite
|
Sign up to set email alerts
|

Seminal Fluid and the Generation of Regulatory T Cells for Embryo Implantation

Abstract: CitationRobertson SA, Prins JR, Sharkey DJ, Moldenhauer LM. Seminal fluid and the generation of regulatory T cells for embryo implantation. Am J

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
140
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(149 citation statements)
references
References 118 publications
(184 reference statements)
1
140
1
7
Order By: Relevance
“…Treg cells are essential for suppressing destructive alloantigenic immunity during pregnancy (Zenclussen 2006;Munoz-Suano et al 2011;Robertson et al 2013). These cells are peripherally induced, as their differentiation depends on both paternal antigens and the conserved noncoding sequence-1 (CNS1) enhancer element that contains a Smad-binding site at the Foxp3 locus (Zheng et al 2010;Rowe et al 2012;Samstein et al 2012).…”
Section: Fetal -Maternal Tolerancementioning
confidence: 99%
See 2 more Smart Citations
“…Treg cells are essential for suppressing destructive alloantigenic immunity during pregnancy (Zenclussen 2006;Munoz-Suano et al 2011;Robertson et al 2013). These cells are peripherally induced, as their differentiation depends on both paternal antigens and the conserved noncoding sequence-1 (CNS1) enhancer element that contains a Smad-binding site at the Foxp3 locus (Zheng et al 2010;Rowe et al 2012;Samstein et al 2012).…”
Section: Fetal -Maternal Tolerancementioning
confidence: 99%
“…Semen provides both male alloantigens and immunomodulatory factors that sufficiently exert biological influences in the FRT, such as activating cytokine gene expression and eliciting changes in the abundance and behavior of infiltrating leukocyte populations. These responses promote tolerance and receptivity for embryo implantation (Robertson 2005;Robertson et al 2013). The mechanisms underlying immunological suppression by semen are not clearly defined but appear related, at least in part, to extremely high concentrations of TGF-b and prostaglandin (PG)E 2 (Robertson et al 2002(Robertson et al , 2009b.…”
Section: Fetal -Maternal Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…This inflammatory response to semen and the associated change in the cytokine environment has been hypothesised to mediate several downstream effects in the female reproductive tract [9]. More recently these studies have been recapitulated in the human, particularly the cervix following intercourse [10][11][12]. Recently we have reported that pregnancies initiated in the absence of seminal plasma in mice give rise to progeny with altered metabolic profiles, obesity and hypertension due in part to perturbations in the peri-conceptional environment and oviduct expression of embryotrophic cytokines [13].…”
Section: Introductionmentioning
confidence: 99%
“…Исходя из этого, HLA-G является ключевой молекулой, обеспечивающей иммунные взаимодействия ма-точного микроокружения с аллогенными HLA эмбриона, а нарушения ее экспрессии будут приводить к индукции тератогенеза, связанно-го с фоновыми ксенобиотическими нагрузками. Исследователями показана связь материнского полиморфизма HLA-G 3'UTR 14-bp ins/del с вер-тикальной передачей от матери к эмбриону/плоду резидентных вирусов [14]. Ранняя активация у ма-тери и эмбриона геномов вирусов может способ-ствовать манифестации тератогенеза [15,16,17].…”
Section: распределение аллелей и генотипов Hla-g 3'utr у женщинunclassified